Efek Ratcheting Pada Anggaran Pemerintah Daerah Provinsi Jawa Timur (Studi Kasus Pada Satuan Kerja Perangkat Daerah Provinsi Jawa Timur) - Dian Puspitasari; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Recently, many problems have been found in the public sector, especially in the budgeting process which uses reference to the previous period's performance targets in preparing the budget. This can lead to slack, decreased performance capacity and manipulation of real activities in budgeting or commonly known as the ratcheting effect. This study aims to test whether there is a ratchet effect in the preparation of the income and expenditure budget. The form of this research is correlational with the type of data used as secondary data obtained from the East Java Local Government SKPD Budget Realization Report for the period (2018-2022). The population and sample used in this study were 37 cities/regencies in East Java Province with purposive sampling technique as the sample. The analytical method uses simple linear regression analysis with the results of the study proving that there is a ratchet effect in the preparation of the income and expenditure budget in the Regional Government of East Java Province.Keywords : Slack, ratchet effect, budget, government budgeting, revenue, local spending